Změna firemní kultury firmy BUWOL METAL s.r.o. - Vrzáček, Tomáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Bakalářská práce se zabývá hledáním návrhů a možností na zlepšení firemní kultury v konkrétní společnosti. Náplní teoretické části práce je popis podnikové kultury a jejího vlivu na výkonnost podniku. Dále pak teoretická část obsahuje možnosti motivace zaměstnanců a zviditelnění společnosti na trhu. V praktické části jsou pak uvedeny výsledky šetření a jsou navrhnuta doporučení, která podporují změnu podnikové kultury.

The aim of this bachelor thesis is to make suggestions and find possbilities of improving the corporation culture in a relavant company. The contenst of the theoretical part are the description of the corporation culture and its influence on the company performance. Then the theoretical part includes motivation possibilities of the employees and the company promotion on the market. The results of the investigation are presented in the practising part. Suggested recommendations that support the change of the corporate structure are also a part of the practising part.
Change of the Corporate Culture of Company BUWOL METAL s.r.o.
Keywords: Firemní kultura; motivace; trh; propagační mix; Firm culture; motivation; market; advertising mix